Planning educational systems for economic growth - Bowles, Samuel (Cambridge, Mass., Harvard University Press, 1969)
This book is about the economics of educational planning. it is largely devoted to consideration of the economic characteristics of the production of educated labor in the schools and its use in the economy.
Bibliographical references: p. 218-220. Bibliographical footnotes.
asm: 21/01/19
Loans
Keywords: Education; Education